2018
DOI: 10.1098/rsos.180298
|View full text |Cite
|
Sign up to set email alerts
|

Towards open data blockchain analytics: a Bitcoin perspective

Abstract: Bitcoin is the first implementation of a technology that has become known as a ‘public permissionless’ blockchain. Such systems allow public read/write access to an append-only blockchain database without the need for any mediating central authority. Instead, they guarantee access, security and protocol conformity through an elegant combination of cryptographic assurances and game theoretic economic incentives. Not until the advent of the Bitcoin blockchain has such a trusted, transparent, comprehensive and gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(18 citation statements)
references
References 11 publications
1
17
0
Order By: Relevance
“…A different type of attack is presented in [20], where the authors show that statistical analysis of bloom filters could help to identify the set of addresses owned by Bitcoin wallets. It has also been shown that patterns of newly minted bitcoins could play a role in revealing information of certain Bitcoin users [15].…”
Section: B Related Workmentioning
confidence: 99%
“…A different type of attack is presented in [20], where the authors show that statistical analysis of bloom filters could help to identify the set of addresses owned by Bitcoin wallets. It has also been shown that patterns of newly minted bitcoins could play a role in revealing information of certain Bitcoin users [15].…”
Section: B Related Workmentioning
confidence: 99%
“…More recently, researchers started a systematic investigation on Bitcoin user interrelations [10] and habits, i.e., the address usage and their strategies to improve the anonymization [2,3], vulnerabilities [11][12][13], and so on, and to allow forensic investigations, to, for instance, identify the origin of scams and illegal activities, such as the case of the blackmail WannaCry, with which criminals required Bitcoin payments to unlock the victim machines [4,5,14].…”
Section: Related Workmentioning
confidence: 99%
“…For sake of illustration, let us now sketch the contributions of some of the papers in this special issue. The paper by McGinn et al [15] argues and demonstrates that the combination of data analytics and data visualization offers a powerful tool box for understanding behaviours and trends on open, permissionless blockchains-here illustrated on Bitcoin.…”
Section: Papers In This Special Issuementioning
confidence: 99%